Adoption of variable rate fertiliser application in the Australian grains industry: Status, issues and prospects - Robertson, M.; Llewellyn, R.; Mandel, Roger; Lawes, R.; Bramley, R.; Swift, L.; Metz, N.; O'Callaghan, C. (Kluwer Academic Publishers, 2012)
Variable rate application of fertiliser (VR) is a practice underpinning a profitable grains industry in Australia. We updated the extent of VR adoption through a national survey (n = 1 130) covering all grain growing regions. Three smaller regional-based surveys (n = 39-102) collected detailed information on the nature and reasoning behind the use of various forms of the technology. We analysed the constraints to the adoption of each step using adoption theory. Surveys showed that 20% of grain growers have adopted some form of VR (varied from 11-35%), up significantly from >5% found 6 years earlier. Adopters are more than likely to have larger farms with a higher area in cropping. Many non-adopters were convinced of the agronomic and economic benefits of VR. A significant proportion of growers were managing within-field variability with manually-operated systems rather than more sophisticated VR technology, and have adopted some form of VR without yield maps, preferring to use soil tests, electro-magnetic induction or their own knowledge of soil and yield variation to define management. The rate of adoption is expected to continue to rise based on greater awareness of the benefits of the technology. The constraints to adoption were technical issues with equipment and software access to service provision and the incompatibility of equipment with existing farm operations.